ANALISIS KINERJA KARYAWAN PADA PT. BANK MANDIRI CLUSTER CILEGON I - Sunarto, Ading (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2019)
Granting compensation against poor, high workload and work dissatisfaction is a failure of the Organization in managing human Resources. So it is very influential on performance of employees. Therefore, company should care on employee performance, with all effort and capital. This study aims to find out the influence of compensation, workload, and job satisfaction on employees performance of PT Bank Mandiri Cluster Cilegon I. Quantitative research methods, used as a research object are PT. Bank Mandiri Cluster Cilegon I, 150 employees that study sample, the sampling technique used is stratified random sampling techniques, research instrument is questionnaire, and a linear regression is used as a method of analysis. The results showed that partially and simultaneously compensation, workload and job satisfaction had significant effect on performance. This finding confirms that performance is achievement of employees in carrying out the duties, so that the reflection is a fair division of tasks and management compensation is good